KETIDAK SETARAAN GENDER DALAM “RE” KARYA MAMAN SUHERMAN : KAJIAN TEORI SARA MILLS - Arianto, Arianto; Syihabuddin, Syihabuddin; Nissa, Barkatun; Bujaya, Muhammad; Kustina, Rika; Talitha, Stella; Trisnawati, Trisnawati; Nina, Nina (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
This study aims to identify, analyze, and synthesize relevant findings in previous studies to build a strong context for further investigation. The method used is a library study to analyze the feminist approach based on Sara Mills' theory, focusing on Subject Position Analysis, Gender Representation in Discourse, Power Relations, and Social and Historical Context. The main character, Re, embodies various subject positions, variously depicted as a victim and a strong figure facing patriarchal domination. The narrative critiques the patriarchal social structure, emphasizing gender inequality that persists across generations. Re's complex character reflects both vulnerability and strength, depicting the tension between her profession as a sex worker and her moral values ​​as a mother. The novel further explores the dynamics of power, particularly through characters such as Mami Lani, who exemplifies the domination of women in a patriarchal system, highlighting the interconnected nature of gender, power, and societal expectations. As such, the narrative serves as a critical examination of sexuality and social injustice.